Veterans Aging Cohort Study (VACS): Overview and description. - Justice, Amy C; Dombrowski, Elizabeth; Conigliaro, Joseph; Fultz, Shawn L; Gibson, Deborah; Madenwald, Tamra; Goulet, Joseph; Simberkoff, Michael; Butt, Adeel A; Rimland, David; Rodriguez-Barradas, Maria C; Gibert, Cynthia L; et al. (Medical care, 2006)
The Veterans Aging Cohort Study (VACS) is a study of human immunodeficiency virus (HIV) infected and uninfected patients seen in infectious disease and general medical clinics. VACS includes the earlier 3 and 5 site studies (VACS 3 and VACS 5) as well as the ongoing 8 site study.
Keywords: Aged; Aging; Cause of Death; Chronic Disease; Cohort Studies; Data Collection; DNA; Female; Focus Groups; Hematologic Tests; HIV Infections; Humans; Interviews as Topic; Male; Medical Records Systems, Computerized; Middle Aged; Patient Selection; Program Development; Prospective Studies; Quality Control; Veterans